Evaluación de los riesgos antrópicos y naturales bajo cumplimiento de normas para las centrales de generación, bocatoma, tanque de presión y subestación península de la EEASA - Rubio Uribe, Diego Mauricio (2019)
This research project is oriented to the development of an anthropic and natural risk assessment, which focused on the realization of a study based on exposure, fragility, resilience, which can have facilities where the main purpose is to know the level of risk to which the Generation, Intake, Pressure Tank and Peninsula Substation are exposed so that through this evaluation, important parameters in question can be made known to the infrastructure that the company owns, since it already has more than 60 years of construction Through the evaluation of anthropic and natural risks, we intend to have a weighting which allows us to have a clear criterion to know if the Generation, Intake, Pressure Tank and Peninsula Substation are at risk, making known which of these facilities It is more vulnerable both in preparation for workers and physical vulnerability, taking into account that the facilities of this Substation is in the lower part of the Peninsula sector where the entrance to the facilities is a stony path and from the paved road to the facilities It is approximately 1km away. The evaluation focuses on an analysis of the year of construction, the construction material, the type of building that are very important parameters for the respective evaluation. The importance of this research project is to safeguard the physical integrity of the workers, knowing the level of preparedness that they have before any natural or anthropic irrigation, in order to take preventive measures and thus be able to protect the most important resource that the Ambato Electric Company has. are the workers who work in the Generation, Intake, Pressure Tank and Peninsula Substation